2014
DOI: 10.1179/2047773214y.0000000148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic resistant bacteria in healthy adults, foods, food animals, and the environment in selected areas in Thailand

Abstract: Objectives: The aim of this study was to determine the prevalence of antibiotic-resistant bacteria, especially extended-spectrum beta-lactamase (ESBL) producing Escherichia coli, in samples from healthy adults, foods, food animals, and the environment in selected areas of Thailand. Methods: Samples were collected from stool specimens from adult food factory and food animal farm workers, fresh and cooked foods sold at markets, rectal swabs of healthy pigs and chickens, fresh pork meat from slaughterhouses, wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
110
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(150 citation statements)
references
References 38 publications
10
110
6
Order By: Relevance
“…The prevalence of ESBL-producing E. coli in fecal samples from healthy pigs (74.8%) was higher compared with healthy layers (6.7%), which was similar to the prevalence found in a previous study [1,3]. The large amount and variety of antimicrobials used on pig farms could indicate that pig farms are a common major source of resistant ESBL-producing E.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The prevalence of ESBL-producing E. coli in fecal samples from healthy pigs (74.8%) was higher compared with healthy layers (6.7%), which was similar to the prevalence found in a previous study [1,3]. The large amount and variety of antimicrobials used on pig farms could indicate that pig farms are a common major source of resistant ESBL-producing E.…”
Section: Discussionsupporting
confidence: 74%
“…When considering geographic areas, the ESBL-producing E. coli prevalence observed in the eastern region of the country was higher than in the north, in contrast with a previous report [3]. The higher prevalence in the north could be a result of variations in study design, different local environments and/or animal production practices [3,19,23].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Apart from the possibility of contamination of animal products by faecal materials during slaughtering and processing, the shedding of resistant organisms into the environment could ultimately lead to the transfer of resistance determinants to environmental microorganisms thus fueling the problems associated with antibiotic resistance. Furthermore, previous studies have shown that selection pressures persisting over a significant number of years could have pre-selected a population of drug-resistant strains before antibiotic use at each farm [47]. Thus, the identification of resistant isolates in the farms under study may not necessarily be the consequence of antibiotic usage in those farms, but might be related to the indiscriminate use of antimicrobial agents over an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…A much higher frequency (73.0 %) of isolation of E. coli was detected in 30 healthy animal farm workers elsewhere [26]. Several studies have reported the similarity of isolates of E. coli regarding the genes and antibiotic sensitivity, recovered from poultry and their human contacts [10,12].…”
Section: Discussionmentioning
confidence: 99%